Estimation of industrial dust using exposure-profiling method - Jia, Qi (Luleå tekniska universitet, Geoteknologi, 2015)
Dust is a primary cause for air quality deterioration, as well as a potential health hazard. Mining and construction sites, in particular, are the most profound in dust generation. The possible source activities are drilling, loading, transporting, dumping, crushing, stockpiles, waste rock and unprotected open surfaces, etc. Dust can be any airborne contaminants occur in the gaseous form or as aerosols. This research dealt with ‘fugitive dust’ which is defined as dust that could not reasonably pass through a stack, chimney, vent, or other functionally equivalent openings, and does not include non-geologic particulate matter emitted directly by internal and external combustion processes. Fugitive dust and dust are used interchangeably in this thesis.In mining areas, construction sites or other industrial areas, fugitive dust is generated through wind erosion of surface materials or application of mechanical forces. The transportation of dust particles is a result of wind direction, velocity, source activities, particles dispersion characteristics, topography, control methods, and so on. A case study on dust fallout from Malmberget Iron Mine showed that the dust generation due to the mining activities in Malmberget Iron Mine influences the down-wind residential areas depending on the weather conditions and the rate of dust generation; the sources of dust generation from Malmberget Iron Mine are haul road transportations, active stockpiles, and the open pit with the loose surface materials. Dust due to wind erosion of the loose material from the open pit is somewhat insignificant as the lab tests showed that the surface material was slightly to moderately erodible and has the soil erosion index of 4.7kg/m2/year.To measure dust generation, three sites were used. They are unpaved roads, road construction and the Aitik tailings dam. This was achieved using an exposure-profiling method with Big Spring Number Eight (BSNE) samplers. Wind erosion prediction system (WEPS) was also used to model the wind erosion process on ...